Measurement of NO in biological samples. (5th September 2014) - Csonka, C; Páli, T; Bencsik, P; Görbe, A; Ferdinandy, P; Csont, T
<x xml:space="preserve">Abstract</x> Although the physiological regulatory function of the gasotransmitter NO (a diatomic free radical) was discovered decades ago, NO is still in the frontline research in biomedicine. NO has been implicated in a variety of physiological and pathological processes; therefore, pharmacological modulation of NO levels in various tissues may have significant therapeutic value. NO is generated by NOS in most of cell types and by non‐enzymatic reactions. Measurement of NO is technically difficult due to its rapid chemical reactions with a wide range of molecules, such as, for example, free radicals, metals, thiols, etc. Therefore, there are still several contradictory findings on the role of NO in different biological processes. In this review, we briefly discuss the major techniques suitable for measurement of NO (electron paramagnetic resonance, electrochemistry, fluorometry) and its derivatives in biological samples (nitrite/nitrate, NOS, cGMP, nitrosothiols) and discuss the advantages and disadvantages of each method. We conclude that to obtain a meaningful insight into the role of NO and NO modulator compounds in physiological or pathological processes, concomitant assessment of NO synthesis, NO content, as well as molecular targets and reaction products of NO is recommended. Linked Articles This article is part of a themed section on Pharmacology of the Gasotransmitters. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2015.172.issue-6